LITERATURE REVIEW : Hubungan Daya Ledak Otot Tungkai Terhadap Keterampilan Menendang Bola Pada Pemain Sepak Bola - Ameliandini Nurrachmah Fadilah (2020)
Kicking a ball is an important basic technique in a soccer game where one releases a shot at the opponent's goal (shooting). One of the goals of playing soccer is to shooting the ball at the opponent's goal. Good game in kicking the ball, related to leg muscle explosive power. Leg muscle explosive power serves to direct the ball precisely, quickly and accurately when making a kick. The purpose of this literature review is to analyze and examine previous research conducted on studies of the relationship to soccer kicking skill in soccer players. The method used in this literature review is the traditional literature review method, which is a complete, critical, and objective analysis related to knowledge or knowledge of a particular topic that does not have a specific method in the library search strategy. Six articles reviewed by the author show the result about the result about the contibution leg muscle explosive power to soccer kicking skill in soccer players. This was concluded based on articles that have been reviewed by the author and on the assessment of quality of articles issued through the SINTA (Sinta and Technology Index) with result showing S3 and S5 values and critical appraisal which gets results with category B values in level of internal validity.